Light spectra of biophilic LED-sourced system modify essential oils composition and plant morphology of Mentha piperita L. and Ocimum basilicum L - Beatrice, Peter; Saviano, Gabriella; Reguzzoni, Marcella; Divino, Fabio; Fantasma, Francesca; Chiatante, Donato; Montagnoli, Antonio (Frontiers in Plant Science, 2023)
Investigating morphological and molecular mechanisms that plants adopt in response to artificial biophilic lighting is crucial for implementing biophilic approaches in indoor environments. Also, studying the essential oils (EOs) composition in aromatic plants can help unveil the light influence on plant metabolism and open new investigative routes devoted to producing valuable molecules for human health and commercial applications. We assessed the growth performance and the EOs composition of Mentha x piperita and Ocimum basilicum grown under an innovative artificial biophilic lighting system (CoeLux®), that enables the simulation of natural sunlight with a realistic sun perception, and compared it to high-pressure sodium lamps (control) We found that plants grown under the CoeLux® light type experienced a general suppression of both above and belowground biomass, a high leaf area, and a lower leaf thickness, which might be related to the shade avoidance syndrome. The secondary metabolites composition in the plants’ essential oils was scarcely affected by both light intensity and spectral composition of the CoeLux® light type, as similarities above 80% were observed with respect to the control light treatments and within both plant species. The major differences were detected with respect to the EOs extracted from plants grown under natural sunlight (52% similarity in M. piperita and 75% in O. basilicum). Overall, it can be speculated that the growth of these two aromatic plants under the CoeLux® lighting systems is a feasible strategy to improve biophilic approaches in closed environments that include both plants and artificial sunlight. Among the two plant species analyzed, O. basilicum showed an overall better performance in terms of both morphological traits and essential oil composition. To increase biomass production and enhance the EOs quality (e.g., higher menthol concentrations), further studies should focus on technical solutions to raise the light intensity irradiating plants during their growth under the CoeLux® lighting systems.